Concentrations of progesterone and conception rates in Holstein heifers after hCG administration during the first 3 weeks after estrus - Stewart, R.E.; Mee, M.O.; Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station, 2012)
We conducted two experiments to determine the effects of administering human chorionic gonadotropin (hCG) on day 4 or on days 15, 16, and 17 after estrus on conception rates and progesterone secretion by the corpus luteum in Holstein heifers. In the first experiment, 60 heifers received hCG or saline on day 4 after estrus and AI. Conception rates were similar between groups. Concentrations of progesterone were increased in treated pregnant and nonpregnant heifers 7 and 14 days after treatment compared with pregnant and nonpregnant controls. In the second experiment, 62 heifers received hCG or saline on days 15, 16, and 17 after estrus and AI. Conception rates again were similar between groups. Concentrations of progesterone were higher in treated pregnant heifers on days 16, 17, and 21 after estrus and in treated nonpregnant heifers on days 17 and 21 compared with pregnant and nonpregnant controls. We conclude that stimulation of the newly formed or mature corpus luteum by hCG increased production of progesterone without affecting conception rates.
Keywords: Dairy; Progesterone; Conception rate; Human chorionic gonadotropin (hCG); Conception rate